Impact of protein or chloride source on Boer goat carcass characteristics - Neufeld, Madeline A.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
With a growing goat population, there is greater emphasis on the role of ingredients to impact carcass composition. The objective of this experiment was to evaluate the impact of protein or chloride source on Boer goat carcass characteristics. Growing goats were fed one of five isocaloric and isonitrogenous diets for 42 days prior to slaughter. Diets included: 1) soybean meal with ammonium chloride; 2) dried distillers grains with solubles with ammonium chloride; 3) SoyPlus with ammonium chloride; 4) soybean meal with SoyChlor; and 5) SoyPlus with SoyChlor. Fifty goats (ten per treatment) were slaughtered in a USDA-inspected facility, with carcass data collected initially (HCW) or after a 24-hour chill. Data were analyzed using the GLIMMIX procedure on SAS, with goat as the experimental unit. Differences in final body weight were not detected among dietary treatments (P=0.284), nor were there differences in hot carcass weight or carcass yield (P>0.05). Goats fed diets with soybean meal, regardless of chloride source, had greater (P<0.05) loin eye area than those fed diets with SoyPlus and SoyChlor. There was no detected impact of dietary treatment (P>0.05) on goat backfat depth or body wall thickness. In summary, ingredient type has limited impact on goat carcass characteristics when calorie and crude protein levels are held constant. However, goats fed soybean meal-based diets had greater loin eye area than those fed SoyPlus and SoyChlor.
Keywords: Fall 2018